6-7 gadus vecu bērnu lasītprasmes sekmēšana sadarbībā ar vecākiem pirmsskolas izglītības iestādē - Gorožniece, Ramona (Latvijas Universitāte, 2025)
Mērķis: Sekmēt 6-7 gadu vecu bērnu lasītprasmi sadarbībā ar vecākiem pirmsskolas izglītības iestādē. Teorētiskajā daļā analizēta literatūra par 6-7 gadus vecu bērnu lasītprasmi un lasītprasmes sekmēšanas iespējām sadarbībā ar vecākiem pirmsskolas izglītības iestādē. Analizēta bērna kognitīvā, emocionālā un sociālā attīstība. Empīriskajā daļā pēc izstrādātajiem kritērijiem veikta sākotnējā lasītprasmes vērtēšana, aprakstītas izmēģinājuma darbības, veikta atkārtota lasītprasmes izvērtēšana un veikti secinājumi. Darba apjoms: 36 lpp., 5 tabulas, 3 attēli, 9 pielikumi, 36 literatūras avoti.

Aim: To promote the reading skils og 6-7- year- old children through collaboration with parents in a preschool educational institution. The qualification paper explores the development of reading skills in 6-7-year-old children and oportunities to enhance these skills through active cooperation with parents within the preschool enviroment. The theoretical part includes an analysis of scientific literature on reading skills development in early childhood, focusing on the cognitive, emotional, and social aspects of child development, as well as the significance of parent- teacher collaboration in the learning process. The empirical part presents an initial assessment of children’s reading skills based on specific criteria, describes trial activities implemented to support reading development, and includes a repeated evaluation followed by conclusions on the effectiveness of parent involvement in supporting children’s reading progress. Volume of the paper: 36 pages, 5tables, 3 images, 9 attachments, 36 sources of literature.
Enhancing the reading skills of 6-7-year-old children through collaboration with parents in a preschool educational institution
Keywords: Izglītības zinātnes; lasītprasme; 6-7 gadus veci bērni; sadarbība; vecāki